Adiantic acid, a new unsaturated fatty acid with a cyclopropane moiety from Adiantum flabellulatum L. Issue 9 (3rd May 2022) - Chen, Junping; Li, Yichen; Cao, Jianguo; Huang, Jinwen; Jiang, Can; Dai, Xiling; Huang, Guozheng
Abstract: Phytochemical investigation of Adiantum flabellulatum L. led to the isolation of four natural compounds, including a novel unsaturated fatty acid with a cyclopropane moiety, i.e. ( S, E )-7-(2-octylcyclopropylidene)heptanoic acid (1 ), together with three known compounds, isoadiantol B (2 ), stigmast-4-en-6 β -ol-3-one (3 ), β -sitosterol (4 ). Compound 3 was isolated from the A. flabellulatum L. for the first time. The structure of 1 was elucidated following a comprehensive analysis of spectroscopic analyses including MS, 1 D and 2 D NMR, and by a mass spectrometry experiment of the dimethyl disulfide (DMDS) adduct, while the known compounds were identified by comparisons with those reported in the literature. Enzyme evaluation of 1 indicated this compound possesses anti- protein tyrosine phosphatase (PTP1B) activity with an IC50 value of 6.99 ± 0.41 μM in vitro . Graphical Abstract: